Komodifikasi Budaya dalam Tayangan Televisi - Mohammad Zamroni (Program Studi Ilmu Komunikasi, 2006)
The aim of the media may have sacred or profane, materially and spiritually, lasting and temporary characteristics. However, media should be related with social control and order. As consequence, media also can be used for many aims that somewhat different by various interests, groups and community sector. We need the existence of mass media anyway, as source of information, entertainment, persuasion, cultural transmission, to motivate social cohesion, control, correlation, and social inheritance. Otherwise, the problem will be different when the mass media has great importance from various groups whether the authorities, capitalists, media workers and others, that on the contrary put them on “top of the top”. It means the community interest as public who in fact become the object has been badly emasculated. With the excuse to preserve the continuity of media industry, the mass media performs commodities in all aspect of human live such as economy, politic, social, culture, and even has spread into religion.